The Circular Model of Some in Instagram Management(Case Study: Forum Human Capital Indonesia) - Alexander, Jessica Lea; Safitri, Dini; Anindhita, Wiratri (UI Scholars Hub, 2021)
The social media is used by companies or organizations to carry out communication activities, such as publication, public relations, promotions, etc. The purpose of this study is to describe the management of Instagram @fhci.bumn by the Forum Human Capital Indonesia’s communication team. The management of such account was studied through The Circular Model of Some. This descriptive research applied a qualitative approach. This study used a non-probability sampling technique by considering the subjectivity of the informants related to the research. In this study, data collection methods were applied, such as in-depth interviews, observations, and documentation. This study concluded that: In accordance with the share stage, the communication team of the FHCI has a definite background and purpose from their Instagram; they have a target from Instagram which is human capital activists and job seekers; in building public trust they display company information on their profiles and collaborate with the Ministry of State-Owned Enterprises for their content. At the optimize stage, the communication team continued to monitor the conversation manually; content was created based on what was currently trending but still considered the audiences’ wishes; they opened discussion space for followers and maintained communication with followers. At the manage stage, media monitoring was carried out manually and only utilized the Instagram features, quick response and optimal real-time interaction because the communication team responded as soon as possible. In the engagement process, there were already brand influencers, namely Erick Thohir and Alexandra Askandar, and they had interactive content, crossword puzzles. Media sosial digunakan oleh perusahaan atau organisasi untuk melakukan kegiatan komunikasi, seperti publikasi, hubungan masyarakat, promosi, dll. Tujuan dari penelitian ini adalah untuk mendeskripsikan pengelolaan Instagram @fhci. BUMN oleh tim komunikasi Forum Human Capital Indonesia. Pengelolaan akun tersebut dikaji melalui The Circular Model of Some. Penelitian deskriptif ini menerapkan pendekatan kualitatif. Penelitian ini menggunakan teknik non-probability sampling dengan mempertimbangkan subjektivitas informan yang terkait dengan penelitian tersebut. Dalam penelitian ini diterapkan metode pengumpulan data, seperti wawancara mendalam, observasi, dan dokumentasi. Penelitian ini menyimpulkan bahwa: Sesuai dengan tahap share, tim komunikasi FHCI memiliki latar belakang dan tujuan yang pasti dari Instagram mereka; mereka memiliki target dari Instagram yaitu human capital activists dan job seeker; dalam membangun kepercayaan publik mereka menampilkan informasi perusahaan pada profil mereka dan berkolaborasi dengan Kementerian Badan Usaha Milik Negara untuk konten mereka. Pada tahap pengoptimalan, tim komunikasi terus memantau percakapan secara manual; konten dibuat berdasarkan apa yang saat ini sedang tren tetapi masih mempertimbangkan keinginan audiens; mereka membuka ruang diskusi bagi pengikut dan menjaga komunikasi dengan pengikut. Pada tahap manage, media monitoring dilakukan secara manual dan hanya memanfaatkan fitur Instagram, respon cepat dan interaksi real-time yang optimal karena tim komunikasi merespons sesegera mungkin. Dalam proses engagement, sudah ada brand influencer, yaitu Erick Thohir dan Alexandra Askandar, dan mereka memiliki konten interaktif, teka-teki silang.